2008
DOI: 10.1103/physrevb.78.073406
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotron radiation and emission in graphene

Abstract: Peculiarity in the cyclotron radiation and emission in graphene is theoretically examined in terms of the optical conductivity and relaxation rates to propose that graphene in magnetic fields can be a candidate for realizing the Landau-level laser, proposed decades ago ͓H. Aoki, Appl. Phys. Lett. 48, 559 ͑1986͔͒.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 22 publications
1
49
0
Order By: Relevance
“…The magneto-optical conductivity of graphene and its cyclotron response have been studied within the linear response theory in a number of publications [9,10,11,12,13]. Intensive experimental studies of the CR in graphene (as well as other electrodynamic phenomena) have been hampered until recently by the absence of graphene flakes of sufficiently large area.…”
mentioning
confidence: 99%
“…The magneto-optical conductivity of graphene and its cyclotron response have been studied within the linear response theory in a number of publications [9,10,11,12,13]. Intensive experimental studies of the CR in graphene (as well as other electrodynamic phenomena) have been hampered until recently by the absence of graphene flakes of sufficiently large area.…”
mentioning
confidence: 99%
“…The optical response of QHE system is now attracted growing interest. For instance, the cyclotron emission from graphene QHE system has been studied theoretically 28 as well as experimentally with infrared transmission. 29 Specifically, Morimoto et al 30 have shown that the optical Hall conductivity σ xy (ω) has a Hall plateau structure even in the ac (∼ THz) regime, both in the ordinary two-dimensional electron gas (2DEG) and in graphene in the quantum Hall regime, although the plateau height is no longer quantized in ac.…”
mentioning
confidence: 99%
“…There is also a proposal for the Landau level laser that exploits the transitions between the Landau levels, which was originally proposed for the ordinary 2DEGs (Aoki, 1986;Morimoto et al, 2008). Extensions are also being made for bilayer graphene, where the particle becomes massive, and for manybody physics including FQHE.…”
Section: Qhe In Graphenementioning
confidence: 97%